Changes in the nutritional statuses of edentulous elderly patients after new denture fabrication with and without providing simple dietary advice. Issue 3 (July 2019) - Suzuki, Hiroyuki; Kanazawa, Manabu; Komagamine, Yuriko; Iwaki, Maiko; Amagai, Noriko; Minakuchi, Shunsuke
Abstract: Purpose: Providing appropriate dental prostheses and dietary interventions may improve food and nutrient intake in elderly edentulous patients, but evidence to support their use is scarce. In this trial, we aimed to clarify the combined effect, on the nutritional statuses of edentulous elderly patients, of dentists providing complete dentures with dietary advice. Methods: A randomized-controlled trial was performed on a healthy elderly population who required new complete dentures. All participants had new complete dentures fabricated and were randomly divided into an intervention or a control group. The intervention group received simple dietary advice through standardized patient information leaflets and the control group received advice on denture care only. Nutritional status was assessed using the Mini Nutritional Assessment short-form (MNA-SF) before and at 3 and 6 months after treatment. At each assessment point, the MNA-SF scores were compared using the Mann–Whitney U test. The within-group differences in the MNA-SF scores were analyzed using the Wilcoxon signed-rank test with Bonferroni correction. Results: In total, 59 participants completed all trial steps. At 6 months after treatment, the MNA-SF score in the intervention group was significantly higher than that in the control group (p = 0.01). Comparing the within-group changes in the MNA-SF score revealed that the score increased significantly from 3 to 6 months in the intervention group (p = 0.001, Bonferroni correction). Conclusions: Nutritional statuses of healthy edentulous elderly population might be improved by fabricating new complete dentures and providing simple dietary advice.